Proceedings of 2015 International Conference on Intelligent Computing and Internet of Things 2015
DOI: 10.1109/icaiot.2015.7111550
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Advanced Metering Infrastructure using cellular communication based on uplink CDMA

Abstract: This paper studies the OkumuraHat propagation model on CDMA technology applied in AMI (Advanced Metering Infrastructure). The aim of this proposal is to get information from the intelligent meter such us: outage management system, status and ratings reading. Prepaid services are oriented to the specific characteristics of rural dwellers. Furthermore, it allows to the energy distribution companies to know the energy consumption in real time. The Okumura -Hata propagation model helps to evaluate a communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Results pointed out the efficiency of the proposed system, confirming a safe environment with low bandwidth requirements. Still regarding the application of AMI, in [260] Arias et al also proposed an approach based on LTE technology, while in [261] Kavithakumari et al reported a solution grounded on GSM technology.…”
Section: G Cellular Networkmentioning
confidence: 99%
“…Results pointed out the efficiency of the proposed system, confirming a safe environment with low bandwidth requirements. Still regarding the application of AMI, in [260] Arias et al also proposed an approach based on LTE technology, while in [261] Kavithakumari et al reported a solution grounded on GSM technology.…”
Section: G Cellular Networkmentioning
confidence: 99%